Colombian Psychology: Knowledge, Technique and Controversies; Reconstructions from Social Studies of Science and Technology (2012)
First, a differentiation between psychology as either a source or a subject matter is made through an empirical review. After, the relationship between psychology, its techniques of intervention and the demarcation of Colombian psychology in some academic scenarios is reviewed during the seventies; the circulation of one of those techniques in a local prison is analyzed and some of the tensions around the use of token economies in this scenario is reconstructed. Through the review of institutional files from some Colombian universities, newspapers and the analysis of three interviews, different interest groups are identified as their rhetoric and discourses are addressed. In a general way, interests related to power and administrative issues are proposed as possible mediators and legitimating factors of behavior modification techniques. Finally, categories from Social Studies of Science and Technology are proposed as means for the reconstruction of current and past local psychology and some guidelines for plausible future research in psychology are outlined. / Resumen. En la primera parte, se realiza una distinción entre la psicología como una herramienta de análisis y como objeto de estudio través de una revisión empírica. Posteriormente, se describe la relación entre la psicología, sus técnicas de intervención y su demarcación local en escenarios académicos durante los años setenta. De esta forma se analiza la circulación de una de estas técnicas y se reconstruyen algunas de las tensiones relacionadas con el uso de economías de fichas en una cárcel colombiana. A través de la revisión de archivos institucionales en algunas universidades del país, la consulta de periódicos durante el periodo de relevancia y el análisis de tres entrevistas, se identifican distintos grupos de interés con sus respectivas retóricas y discursos. En términos generales se plantea que algunos intereses asociados al poder constituyeron factores mediadores de la legitimación de las técnicas de modificación de conducta en los escenarios delimitados. Por último, se proponen las categorías de los Estudios Sociales de la Ciencia como medios adecuados para la reconstrucción histórica y actual de la psicología local y se sugieren algunos lineamientos viables para la investigación futura en este campo.